ANALISIS PERENCANAAN PENGEMBANGAN REKAM MEDIS ELEKTRONIK RSUD KOTA YOGYAKARTA DENGAN PENDEKATAN SWOT - PESTEL - Intan Wulandari,; Eny Sulistyowati,; Yepri Endika, (Nusantara Hasana Journal, 2025)
This study aims to analyze the factors influencing the development of Electronic Medical Records (EMR) at RSUD Kota Yogyakarta in 2024 using SWOT and PESTEL analytical approaches. Secondary data were collected from hospital documents and relevant government regulations. The SWOT analysis identifies internal and external factors such as strengths, weaknesses, opportunities, and threats, while the PESTEL analysis examines political, economic, social, technological, environmental, and legal influences on EMR implementation. The findings indicate that the hospital holds considerable potential due to strong managerial support and adequate infrastructure, though challenges remain in terms of limited human resource competencies and data security risks. The integration of both analyses provides strategic recommendations to support the optimization of EMR implementation and enhance the quality of healthcare services.